Application of the Health Belief Model in Adherence to Iron Supplement Consumption Among Female Students at Universitas Diponegoro - Alif, Dzaki Aziz Naufal; Prabamurti, Priyadi Nugraha; Handayani, Novia (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Anemia, a deficiency of red blood cells, is common in adolescent girls. The Indonesian government has an iron supplement program targeting school-aged girls. Female university students are not included. Consequently, iron supplement intake depends on individual choices. This study aimed to identify the factors associated with adherence to iron supplement consumption as a preventive measure against anemia among female students at Universitas Diponegoro.Methods: This was a quantitative study with a cross-sectional approach using interviews and questionnaires. The sample of this study was 384 respondents from 33,156 female students of Universitas Diponegoro in 11 faculties and one vocational school using the proportional sampling method, with the inclusion criteria being active diploma/undergraduate students who consented. This study employed univariate and bivariate analyses using chi-square tests.Results: The results indicated a significant relationship between iron supplement adherence and knowledge of anemia (p=0.001), knowledge of iron tablet consumption (p=0.001), perceived susceptibility (p=0.001), perceived severity (p=0.001), perceived benefits (p=0.001), perceived barriers (p=0.001), self-efficacy (p=0.001), and cues to action (p=0.001). However, no significant relationships were found between iron supplement adherence and age (p=0.570), level of study (p=0.127), allowance (p=0.958), or place of residence (p=0.793).Conclusion: Knowledge of anemia, knowledge of iron tablet consumption, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues to action are associated with iron supplement adherence among female students at Universitas Diponegoro in Semarang.